Narasi Besar dan Narasi Kecil Dalam Pembelajaran IPA SMP: Perspektif Postmodernisme Lyotard - Nugroho, Murwanto Setyo; Mahardhika, Itang Enrico Pradana; Fauziati, Endang (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
This research examines the application of Lyotard's postmodernist perspective in Natural Sciences (IPA) learning to deconstruct big narratives and identify the potential of small narratives. The research method uses a qualitative descriptive approach by collecting data through interviews, classroom observations, curriculum document analysis, and case studies. The aim of the research is to describe Lyotard's postmodernist perspective in deconstructing big narratives, analyzing the impact of big narratives and identifying the potential of small narratives in science learning, analyzing the impact of big narratives in science learning. The research results show that grand narratives provide a broad conceptual framework that helps students understand global issues. However, these narratives are often abstract and therefore difficult to relate to students' daily lives. In contrast, small narratives involving students' local experiences can make learning more relevant and meaningful. Integrating large and small narratives creates more inclusive, relevant and dynamic learning. Grand narratives provide a global framework, while small narratives bridge abstract concepts with real experiences, increasing learner understanding, motivation, and engagement. This combination not only deepens scientific understanding but also builds students' critical thinking and social responsibility skills. Local project-based learning strategies, simple experiments, and exploration of local wisdom are suggested to optimize the integration of these two narratives.